NEW ASTROMETRIC REDUCTION OF THE SUPERCOSMOS PLATE ARCHIVE: FIRST RESULTS - Akhmetov, V. S.; Andruk, V. M.; Protsyuk, Yu. I.; Relke, H.; Eglitis, I. (Одеські астрономічні публікації, 2019)
The arrivals of the new more accuracy reference catalogues and also development of new meth- ods and approaches for reduction astrometric data give the new life for photographic plates archives. Gaia DR2 is not only a giant step in the astrometric accuracy allowing to measure new objects also provides plates archives ob- served in the past with modern accuracy. In this work we present the first results of astrometric reduction in the sys- tem of Gaia DR2 for some photographic plates that were obtained by UK Schmidt telescope (UKST) and digitized by the SuperCOSMOS scanning machine. The UKST is a classical Schmidt with the following parameters: mirror diameter 1.83m; focal length 3.07m; photographic plate size 356mm square, covering 6.4 x 6.4 degrees of sky; plate scale 67.12 arcsec/mm. To date the UKST has taken over 17,000 plates, the plates are stored in the Plate Li- brary at the Royal Observatory, Edinburgh. The photo- graphic plates are digitized to 15 bits (32768 grey levels) with a resolution of 10 microns (0.67 arcsec)/pixel). Each digitized Schmidt plate has size 32256x32256 pixels and produces about 2 Gbyte pixel data .. We are making new reduction of photographic plates that allowing to provide valuable data for future researches in astrometry as well as in astrophysics. The obtained astrometric and photometric data from photographic plates were compared with same one from modern catalogues.